(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article discusses the theoretical aspects of studying the picture of the world and its components. It analyzes the definitions of the language picture of the world, attention is paid to the distinctive features of the phraseological picture of the world and the need to compare the phraseological units of different languages is justified in order to identify the actual national features of the perception of the value.